Enter Modular Exponentiation


      

Solve 36 mod 11 using:

Modular exponentiation

Build an algorithm:

n is our exponent = 6

y = 1 and u ≡ 3 mod 11 = 3

See here

n = 6 is even

Since 6 is even, we keep y = 1

Determine u2 mod p

u2 mod p = 32 mod 11

u2 mod p = 9 mod 11

9 mod 11 = 9
Reset u to this value

Cut n in half and take the integer

6 ÷ 2 = 3

n = 3 is odd

Since 3 is odd, calculate (y)(u) mod p

(y)(u) mod p = (1)(9) mod 11

(y)(u) mod p = 9 mod 11

9 mod 11 = 9
Reset y to this value

Determine u2 mod p

u2 mod p = 92 mod 11

u2 mod p = 81 mod 11

81 mod 11 = 4
Reset u to this value

Cut n in half and take the integer

3 ÷ 2 = 1

n = 1 is odd

Since 1 is odd, calculate (y)(u) mod p

(y)(u) mod p = (9)(4) mod 11

(y)(u) mod p = 36 mod 11

36 mod 11 = 3
Reset y to this value

Determine u2 mod p

u2 mod p = 42 mod 11

u2 mod p = 16 mod 11

16 mod 11 = 5
Reset u to this value

Cut n in half and take the integer

1 ÷ 2 = 0

Because n = 0, we stop

We have our answer

Final Answer


36 mod 11 ≡ 3